Film as an educational tool in medical pedagogy: a study on cinemeducation and its effectiveness - Usama Naveed Cheema; Sarmed Ibrahim; Nukhbat Ullah Awan; Haram Ashiq; Wagma Sarmed; Khalid Munir (Journal of the Pakistan Medical Association)
Objective: To find out the possibilities and usefulness of introducing cinemeducation in medical institutions, and to formulate suggestive inserts for faculty and policy-makers.